Genomic and Transcriptomic Investigation of the Physiological Response of the Methylotroph Bacillus methanolicus to 5-Aminovalerate - Haupka, Carsten; Brito, Luciana F.; Busche, Tobias; Wibberg, Daniel; Wendisch, Volker F. (Frontiers in Microbiology, 2021)
The methylotrophic thermophile Bacillus methanolicus can utilize the non-food substrate methanol as its sole carbon and energy source. Metabolism of L-lysine, in particular its biosynthesis, has been studied to some detail and methanol-based L-lysine production has been achieved. However, little is known about L-lysine degradation which may proceed via 5-aminovalerate (5AVA), a non-proteinogenic ω-amino acid with applications in bioplastics. The physiological role of 5AVA and related compounds in the native methylotroph was unknown. Here, we showed that B. methanolicus exhibits low tolerance to 5AVA, but not to related short-chain (C4-C6) amino acids, diamines and dicarboxylic acids. In order to gain insight into the physiological response of B. methanolicus to 5AVA, transcriptomic analysis by differential RNA-Seq in the presence and absence of 5AVA, respectively, were performed. Besides genes of the general stress response, RNA levels of genes of histidine biosynthesis and iron acquisition were increased in the presence of 5AVA, while an Rrf2 family transcriptional regulator gene showed reduced RNA levels. In order to test if mutations can overcome growth inhibition by 5AVA, adaptive laboratory evolution (ALE) was performed and two mutants - AVA6 and AVA10 - with higher tolerance to 5AVA were selected. Genome sequencing revealed mutations in genes related of iron homeostasis, including the gene for iron siderophore-binding protein. Overexpression of this mutant gene in the wild-type strain MGA3 improved 5AVA tolerance significantly at high Fe2+ supplementation. The combined ALE, omics, and genetics approach helped elucidating the physiological response of thermophilic B. methanolicus to 5AVA and will guide future strain development for 5AVA production from methanol.